(untitled) (Research, Society and Development, 2022)
This article, a product of the Brazilian Basic School classes, developed in the Graduate Program in Management and Curriculum of the Basic School (PPEB), at the Federal University of Pará (UFPA), aimed to analyze how large-scale assessments in Brazil, carried out by the Basic Education Assessment System (Saeb), are fulfilling their functions to improve the quality of public education. The research methodologically used the bibliographic review of the narrative type, with theoretical foundations based, above all, on Souza, Werle and Carvalho, Carvalho and Junior who address the large-scale evaluation policy in Brazil, which revealed the lack of continuing education for teachers and for the school management team, as well as the emergence of assessment and tutoring industries, curriculum minimization and the transformation of the teacher into a simple learning technician.